Myotonia Congenita: Case Report of Becker's Variant - Okan Akşahin; Mehmet Güney Şenol (Boğaziçi Tıp Dergisi, 2022)
Myotonia is a finding caused by muscle hyperexcitability and occurs as a result of delayed relaxation. The two disease groups in which myotonia is seen are myotonic dystrophy from muscular dystrophies and non-dystrophic myotonias from muscle ion channel diseases. Congenital myotonia is a rare inherited disease of skeletal muscle characterized by diffuse muscle hypertrophy, non-progressive myotonia, and difficulty in relaxation after sudden muscle contraction. In this article, we present a 59-year-old patient, who applied to the neurosurgery clinic due to increased muscle weakness, pain, and muscle stiffness in the legs for the past 1 year, was diagnosed with spinal stenosis and was referred to us before surgery and was diagnosed with myotonia congenita as a result of clinical evaluation and EMG. Congenital myotonia may have a subclinical course in some patients and may be difficult to diagnose in the presence of concomitant symptomatic spinal cord pathology. It is very important to inform anesthesiologists before surgery to prevent perioperative complications when the diagnosis is made.